2013
DOI: 10.1021/jf304926m
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on Antioxidant Activity of Bromophenols from the Marine Red Alga Rhodomela confervoides: H-Atom vs Electron Transfer Mechanism

Abstract: Bromophenols are known as antioxidant radical scavengers for some biomolecules such as those in marine red alga. Full understanding of the role played by bromophenols requires detailed knowledge of the radical scavenging activities in probable pathways, a focus of ongoing research. To gain detailed insight into two suggested pathways, H-atom transfer and electron transfer, theoretical studies employing first principle quantum mechanical calculations have been carried out on selected bromophenols. Detailed inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 42 publications
(86 reference statements)
2
17
0
Order By: Relevance
“…Reis and his co-workers also theoretically evaluated the antioxidant activity of various phenolic compounds using different levels of calculations [9]. Again, Javan et al investigated computationally the H-atom vs electron transfer mechanism for antioxidant activity of some bromophenols and compared their observation to those for which the antioxidant activity was previously evaluated [10]. Analysis of antioxidant activity of various gallic acid derivatives as well as the values of some density-based reactivity descriptors was carried out by Kar et al and they found that phenolic compounds are more stable in gas phase than in solvent medium [11].…”
Section: Introductionmentioning
confidence: 99%
“…Reis and his co-workers also theoretically evaluated the antioxidant activity of various phenolic compounds using different levels of calculations [9]. Again, Javan et al investigated computationally the H-atom vs electron transfer mechanism for antioxidant activity of some bromophenols and compared their observation to those for which the antioxidant activity was previously evaluated [10]. Analysis of antioxidant activity of various gallic acid derivatives as well as the values of some density-based reactivity descriptors was carried out by Kar et al and they found that phenolic compounds are more stable in gas phase than in solvent medium [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the DFT energetics of the parent enediyne reaction reproduced the experimental value to within 1.5 kcal/mol . Density functional theory has also been successful in calculating energetics of H‐atom transfer reactions such as polyphenols exhibiting antioxidant properties . The B3LYP method is also found to be reliable for Garratt‐Braverman cyclizations and intramolecular H‐atom transfer reactions .…”
Section: Methodsmentioning
confidence: 72%
“…[4] Density functional theory has also been successful in calculating energetics of H-atom transfer reactions [13][14][15] such as polyphenols exhibiting antioxidant properties. [16,17] The B3LYP method is also found to be reliable for Garratt-Braverman cyclizations and intramolecular H-atom transfer reactions. [18] When searching for whether diradical 7 existed, uBLYP, uM062X, and uM06 functionals were also used.…”
Section: Methodsmentioning
confidence: 99%
“…is demonstrates the sensitivity of the cation radical forms of isolated ligand (La i ) to the polarity of different solvents used [21,47]. is may be attributed to the lowest value of the enthalpies of solvation of the electron.…”
Section: Electron Transfer Mechanismmentioning
confidence: 94%
“…Until now, there is no study on the impact of the metal chelation of these molecular systems on their antioxidant powers. e characterization of the antioxidant activity for large number of antioxidants RX-H, [18][19][20][21][22] has been done by the calculation of the RX-H (X � donor atom such as O, N, ...) bond dissociation enthalpy (BDE). From these calculations, the prediction of the relationship structure-activity and the design of novel possible antioxidant have been carried out.…”
Section: Introductionmentioning
confidence: 99%